Genetically Predicted Obesity Causally Increased the Risk of Hypertension Disorders in Pregnancy - Wang, Wenting; Tan, Jiang-Shan; Hua, Lu; Zhu, Shengsong; Lin, Hongyun; Wu, Yan; Liu, Jinping (Frontiers in Cardiovascular Medicine, 2022)
Aims This study aimed to evaluate the causal association between obesity and hypertension disorders in pregnancy. Methods Two-sample Mendelian randomization (MR) study was conducted based on the data obtained from the GIANT (n = 98,697 participants) consortium and FinnGen (n = 96,449 participants) consortium to determine the causal effect of obesity on the risk of hypertension disorders in pregnancy. Based on a genome-wide significance, 14 single-nucleotide polymorphisms (SNPs) associated with obesity-related databases were used as instrumental variables. The random-effects inverse-variance weighted (IVW) method was adopted as the main analysis with a supplemented sensitive analysis of the MR-Egger and weighted median approaches. Results All three MR methods showed that genetically predicted obesity causally increased the risk of hypertension disorders in pregnancy. IVW analysis provided obesity as a risk factor for hypertension disorders in pregnancy with an odds ratio (OR) of 1.39 [95% confidence interval (CI) 1.21–1.59; P = 2.46 × 10−6]. Weighted median and MR Egger regression also showed directionally similar results [weighted median OR = 1.49 (95% CI, 1.24–1.79), P = 2.45 × 10−5; MR-Egger OR = 1.95 (95% CI, 1.35–2.82), P = 3.84 × 10−3]. No directional pleiotropic effects were found between obesity and hypertension disorders in pregnancy with both MR-Egger intercepts and funnel plots. Conclusions Our findings provided directed evidence that obesity was causally associated with a higher risk of hypertension disorders in pregnancy. Taking measures to reduce the proportion of obesity may help reduce the incidence of hypertension disorders in pregnancy.